2022
DOI: 10.1002/btm2.10402
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid‐g‐lipoic acid granular gel for promoting diabetic wound healing

Abstract: Diabetic patients are prone to developing chronic inflammation after trauma and have persistent nonhealing wounds. Reactive oxygen species (ROS) and recurrent bacterial infections at the site of long-term wounds also further delay skin wound healing and tissue regeneration. In this study, a granular gel (which exhibits ROS scavenging and antibacterial properties) is fabricated based on hyaluronic acid-g-lipoic acid (HA-LA). Briefly, HA-LA is synthesized to fabricate HA-LA microgels, which are further assembled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Strain scanning measurements were carried out at a constant frequency of 1 Hz and a strain range from 0.1% to 1000%. The shear‐thinning behavior was studied by measuring the viscosity change with the shear rate increased from 0.001 to 100 s −1 continuously 25 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strain scanning measurements were carried out at a constant frequency of 1 Hz and a strain range from 0.1% to 1000%. The shear‐thinning behavior was studied by measuring the viscosity change with the shear rate increased from 0.001 to 100 s −1 continuously 25 …”
Section: Methodsmentioning
confidence: 99%
“…The shear-thinning behavior was studied by measuring the viscosity change with the shear rate increased from 0.001 to 100 s À1 continuously. 25 For the swelling test, the vacuum-dried granular hydrogels were weighted and immersed in deionized water at 25 C and weighed at 5, 10, 30, 60, 180, 300, 600, and 1800 s. The swelling ratio was calculated according to the following formula: SR = (W x -W 0 )/W 0 , where W x was the wet weight of the hydrogels at different time points, and W 0 was the dry weight of the hydrogels. 25…”
Section: Preparation Of Granular Hydrogelmentioning
confidence: 99%
“…Moreover, the antimicrobial activity test showed that the HA-LA granular gel inhibited the growth of S. aureus due to the presence of Ag+. Finally, in vivo experiments demonstrate that the HA-LA granular gel effectively reduces excessive ROS at the wound site, enhances the secretion of reparative growth factors, and significantly accelerates both common and diabetic wound healing [ 195 ].…”
Section: Applications Of Antioxidant-incorporated Hydrogels In Chroni...mentioning
confidence: 99%
“…can be used for the design of interaction between micro-particles due to their bonding and breaking ability under mild conditions. 1518…”
Section: Introductionmentioning
confidence: 99%
“…can be used for the design of interaction between micro-particles due to their bonding and breaking ability under mild conditions. [15][16][17][18] Collagen (COL), the main component of musculoskeletal tissue and forms the ECM of most tissues, is one of the most attractive polymers, which has been widely used in tissue engineering. 19 COL-based hydrogels are favorable for tissue engineering purposes, because COL is highly biocompatible and abundant, which makes it the material of choice for many wound healing studies.…”
Section: Introductionmentioning
confidence: 99%